GE_GERICHTE C/21310/2012 vom 23. November 2015 - GE Cour de justice (2015)
BAIL À LOYER; LOCAL PROFESSIONNEL; RÉSILIATION ABUSIVE; PROLONGATION DU BAIL À LOYER | CO.271.1; Cst.29.2; CO.272; CPC.95.1.a; CPC.95.2; CPC.116.1; LaCC.22.1